Randomized trial on the impact of card Game-Based teaching on learning and memory retention of neurological syndromes - Xi Yu; Jiafu Wu; Yuhuan Zhang; Zhixin Di; Wanling Nie; Mingyu Wang; Xingyu Zhu; Yunkai Zhang; Yimeng Wu; Yan Ma; Yuxi Han; Miao Yu (BMC Medical Education)
Abstract Background Learning about neurological syndromes is an essential component of medical education, but traditional teaching methods often lack interactivity and practical engagement. This study investigates the impact of an innovative teaching approach using the Neurological Syndrome Card Game (NSCG) on students’ learning outcomes. Methods A randomized controlled trial design was implemented, with participants divided into an experimental group and a control group. The control group received traditional lecture-based instruction (e.g., PowerPoint presentations and case analyses), whereas the experimental group engaged in NSCG-based learning. The game involved card-matching competitions and anatomical injury location tasks to enhance students’ recognition, understanding, and memory of neurological syndromes. Learning outcomes were evaluated through assessments of learning effectiveness, knowledge retention rates, cognitive load, and learning experience. Results A total of 48 students participated in the study. No significant differences were found in baseline characteristics between the groups. Following the intervention, the experimental group showed significantly better immediate learning effects at 1 week (13.33 ± 2.12 vs. 11.92 ± 1.44, t = 3.344, P = 0.002), 3 weeks (12.83 ± 2.04 vs. 10.63 ± 1.86, t = 3.923, P = 0.000), and 6 weeks (10.04 ± 1.20 vs. 7.79 ± 1.61, t = 5.484, P = 0.000). In terms of long-term memory retention, the experimental group demonstrated superior knowledge retention rates at all time points: 22.53% at week 1, 29.49% at week 3, and 31.12% at week 6. Regarding cognitive load, the experimental group exhibited significantly lower total scores (46.96 ± 1.65 vs. 69.08 ± 4.06) and scores across all dimensions (P < 0.05). Evaluations of the learning experience indicated that students in the experimental group rated their interest and memory outcomes more positively. Conclusion The NSCG-based teaching method significantly enhances students’ learning and memory retention of neurological syndromes, reduces cognitive load, and increases learning interest. This method may be a useful approach for enhancing clinical syndrome teaching in medical education.